Book Review - Alexander M. Volk (Names)
The Boggart: Folklore, History, Place-Names and Dialect. By Simon Young. Exeter: University of Exeter Press. 2022. Pp. 229 (Hardback). £60. ISBN: 978-905826-90-3.